Perception of undergraduates and dentists about the waste generated in the dental clinic and its environmental impact: an Integrative Review (Research, Society and Development, 2021)
Objective: The objective of this study was to verify the knowledge of undergraduates of Dentistry and dentists about the residues generated after clinical care and its environmental impact. Methodology: This is an integrative review, whose search strategy was based on the use of words and descriptors Dentistry and selected articles published in the Portuguese language, English and Spanish, available in full and online in databases PubMed and SciELO, besides, MEDLINE, LILACS and BBO track BVS and comprised in the year 2008 to 2019, collected in the months of February to March 2021. Among the 49 titles and after applying filters, reading titles and abstracts and removing duplicates, totaled 8 studies to compose this review. Results: The most studies pointed out gaps in knowledge about RSS, whether among undergraduate students or dentists, and when their knowledge was favorable, few attitudes were taken on this issue. Conclusion: The environmental education in clinical practice is not yet a reality experienced daily in dentistry universities, nor practiced by dentists. Thus, the need for interventionist actions in health in the academic and professional scope is evident, aiming at behavioral change and favoring environmental sustainability.